Characterization and monitoring by droplet digital PCR of a novel BCR-ABL1 fusion transcript in a patient with chronic myeloid leukemia. Issue 5 (2020) - Petiti, J; Dragani, M; Castelli, A; Lacono, M Lo; Fantino, C; Badino, C
No abstract available